The disruptive power of online education : challenges, opportunities, responses - Altmann, Andreas, 1963-; Ebersberger, Bernd; Mössenlechner, Claudia; Wieser, Desiree (Emerald Publishing Limited, 2018)
The higher education sector is being disrupted through the effect thattechnological innovations have on the educational market. As digital and mobiletechnologies are developing further, higher education institutions must embracethese developments to meet the needs of their learners and to not becomeirrelevant. In higher education, disruptive effects are mainly visible on aprogram/product level, with an increasing number of programs including someelement of online education.Disruptive effects also become evident on a pedagogical level, wherestudent engagement, collaboration and social learning, gamification and seriousgames, competency-based learning, teacher training, and overcoming geosocialdivides are high on the agenda. This book considers the effect of onlineelements and their design on university business models andinternationalization, course design, massive open online courses (MOOCs), andthe scalability of online programs. It also explores how higher educationinstitutions across the globe respond and react to the challenges andopportunities evolving in online education.
Includes index.
Keywords: Internet in education.; Computer-assisted instruction.; Computer networks.; Educational technology.; Education -- Computers & Technology.; Educational equipment & technology, computer-aided learning (CAL).; elektronické knihy; electronic books